2016
DOI: 10.1111/jcpt.12479
|View full text |Cite
|
Sign up to set email alerts
|

The optimal single-dose regimen of rasburicase for management of tumour lysis syndrome in children and adults: a systematic review and meta-analysis

Abstract: SUMMARYWhat is known and objective: To perform a meta-analysis exploring the optimal single-dose regimen for managing tumour lysis syndrome (TLS) in children and adults with haematological malignancies. Methods: We systematically searched PubMed, MEDLINE, Web of Science, the Cochrane Library and the ClinicalTrials.gov website for studies regarding single-dose rasburicase in paediatric and adult patients with TLS. Data were analysed using Open MetaAnalyst statistical software. Results: Fifteen adult studies (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
(87 reference statements)
0
27
0
2
Order By: Relevance
“…The recommended dose of rasburicase is 0.15 to 0.2 mg/kg daily (maximum dose of 6 mg per our institutional guidelines) with a duration of therapy from 1 to 7 days. 17,18 Our patient's initial clinical presentation with a large tumor burden, diagnosis of T cell lymphoma, and significant risk of continued rise in uric acid with initiation of chemotherapy, placed him at a high risk for complications related to TLS. Given these concerns, therapy with rasburicase was administered.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended dose of rasburicase is 0.15 to 0.2 mg/kg daily (maximum dose of 6 mg per our institutional guidelines) with a duration of therapy from 1 to 7 days. 17,18 Our patient's initial clinical presentation with a large tumor burden, diagnosis of T cell lymphoma, and significant risk of continued rise in uric acid with initiation of chemotherapy, placed him at a high risk for complications related to TLS. Given these concerns, therapy with rasburicase was administered.…”
Section: Discussionmentioning
confidence: 99%
“…The results of 2 such studies by Jayabose et al [16] and Gopakumar et al [17], which Cho et al referenced in their decision to use a median dose of only 0.1 mg/kg, show inferior responses to those obtained with the recommended dose. A recent review and meta-analysis by Yu et al concluded that doses of 0.15 or 0.20 mg/kg are needed to produce excellent responses in young children with HU [18], confirming the findings reported by Pui et al [14].…”
Section: Response To Rasburicase In Children With Tumor Lysis Syndromementioning
confidence: 52%
“…Alternatively, for patients with the low to moderate risk, a single fixed (3, 4.5, 6, or 7.5 mg) or weightbased (0.15-0.20 mg/kg) dose regimen has been proposed, and its efficacy is demonstrated [82][83][84][85][86][87][88]. A systematic review and meta-analysis of 19 studies by Yu et al [89] revealed that single doses of rasburicase: 6 mg for adults and 1.5 and 0.15 mg/kg for children, were sufficient to normalize and sustain lower uric acid and creatinine levels in adults with TLS. According to these authors, the 3-and 4.5-mg single doses can be considered if the baseline uric acid level is <12 mg/dL.…”
Section: Rasburicasementioning
confidence: 99%
“…According to these authors, the 3-and 4.5-mg single doses can be considered if the baseline uric acid level is <12 mg/dL. In patients treated with the single-dose regimen, a reassessment of clinical and biochemical parameters is necessary, with repeating the dose if required [3,89]. Cortes et al [90] demonstrated that sequential therapy with rasburicase followed by allopurinol was similarly effective and may be a reasonable and cost-effective approach with similar efficacy in adults with hyperuricemia or at high risk for TLS.…”
Section: Rasburicasementioning
confidence: 99%